Effect of Training Systems on Accumulation of Flavan-3-ols in Cabernet Sauvignon Grape Seeds at the North Foot of Mt. Tianshan - Liu, Y.; Yan, J.; Li, Q.; Wang, J.; Shi, Y. (South African Journal of Enology and Viticulture, 2018)
development of Cabernet Sauvignon grapes during two consecutive seasons (2011 to 2012) in the northwest of China was evaluated. The applied training systems include the modified vertical shoot positioned (M-VSP); the fan training system with two trunks (F-TT); and the fan training system with multiple trunks (F-MT). The results show that the pattern of flavan-3-ol accumulation was similar for the three training systems in both vintages, with flavan-3-ols being the highest around véraison, before declining as harvest approaches. Compared to the 2011 vintage, the dry vintage of 2012 had a greater accumulation of total flavan-3-ols and individual flavan-3-ol monomers, including (+)-catechin (C), (-)-epicatechin (EC) and (-)-epicatechin-3-O-gallate (ECG). With regard to the effect of training systems, M-VSP contributed to a significantly higher content of total flavan-3-ols, while the percentage of ECG was lower for M-VSP. As for the three flavan-3-ol units (terminal subunits, extension subunits and monomers), the 2012 vintage was more likely to accumulate extension subunits and monomers, and the effect of training system on these three flavan-3-ols units varied between the different vintages. Meanwhile, the proportion of ECG in terminal subunits and of C in extension subunits was higher in 2012, whereas the training system of F-TT had a higher percentage of ECG in extension subunits in both vintages. In addition, the effect of vintage on the composition of flavan-3-ols in harvested grape seeds was more obvious than that of the training system.